2011
DOI: 10.1074/jbc.m110.203307
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase SETD3 Regulates Muscle Differentiation

Abstract: Histone lysine methylation, as one of the most important factors in transcriptional regulation, is associated with a various physiological conditions. Using a bioinformatics search, we identified and subsequently cloned mouse SET domain containing 3 (SETD3) with SET (Su(var)3-9, Enhancer-of-zeste and Trithorax) and Rubis-subs-bind domains. SETD3 is a novel histone H3K4 and H3K36 methyltransferase with transcriptional activation activity. SETD3 is expressed abundantly in muscular tissues and, when overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 28 publications
5
105
1
Order By: Relevance
“…Similarly, enzymes that determine levels of methylation of histones have also been shown to regulate myogenic differentiation. SET7 and SETD3, which can methylate H3-K4 and often mark actively transcribed region, interact with MyoD to target muscle specific genes and thereby promote differentiation of myoblast cells [10,11]. In contrast, Suv39h1 that target H3-K9 and the polycomb protein Ezh2 that mediates methylation of H3-K27 inhibit myogenic differentiation by repressing muscle specific genes, while another H3-K9 specific histone methyltransferase (HMTase) G9a targets nonhistone substrates such as MEF2D and MyoD to inhibit the formation of differentiated myofibers [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, enzymes that determine levels of methylation of histones have also been shown to regulate myogenic differentiation. SET7 and SETD3, which can methylate H3-K4 and often mark actively transcribed region, interact with MyoD to target muscle specific genes and thereby promote differentiation of myoblast cells [10,11]. In contrast, Suv39h1 that target H3-K9 and the polycomb protein Ezh2 that mediates methylation of H3-K27 inhibit myogenic differentiation by repressing muscle specific genes, while another H3-K9 specific histone methyltransferase (HMTase) G9a targets nonhistone substrates such as MEF2D and MyoD to inhibit the formation of differentiated myofibers [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we conclude that the SETD3 protein is a fully active HMT for H3 with its activity dependent on the SET domain. Recently, independent studies also identified the zebrafish and mouse Setd3 genes via a bioinformatics approach 18,19 which also haematologica | 2013; 98(5) showed that SETD3 has HMT activity, in particular, on H3K4 and H3K36. 18 These studies used several H3 peptides instead of nucleosomes as substrates for the HMT assay.…”
Section: Functions Of Setd3 In Histone Modificationmentioning
confidence: 99%
“…Chem. (2016) 8(13) future science group Review Rogawski, Grembecka & Cierpicki SETD3 is a poorly characterized putative tumor suppressor that methylates H3K4 and H3K36 in vitro and in SETD3-transfected cells [117]. SETD3 expression is lower in renal cell tumors than normal renal tissues, and low expression of SETD3 is associated with shorter survival in renal cell carcinoma patients [118].…”
mentioning
confidence: 99%